STRATEGI KOMUNIKASI POLISI RESORT KOTA PEKANBARU DALAM MENGATASI GENG MOTOR - Musyarofah Dewi Utami; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Boy and adolescent be nation router generation. but there are some boy/adolescent disagree with our hope, many between they are in concerned motor gang. Motor gang many scattered to socialized can not be let off hand and necessary looked for solution or manner to overcome it. In overcome motor gang necessary involvement all sides, one of them Policeman side Resort city Pekanbaru as side that has duty to give security with freshmen for society especially at city Pekanbaru. Efforts that done by Polresta Pekanbaru among others with do communication towards society. In do communication of course has certain strategies by desirable aim. This watchfulness aims to detect to how Policeman communication strategy Resort city Pekanbaru in overcome motor gang, with everything factor that causes the slow Policeman Resort city Pekanbaru in overcome motor gang at city Pekanbaru.This watchfulness uses qualitative method that is data collecting that is got based on fact that pass observation, interview, and documentation. where informant in this watchfulness number 11 person, consist of (Kapolresta Pekanbaru, unit head Binaan Society, a unit Staff Binaan society, traffic unit head, a traffic unit staff, teacher, society, siswa-siswi dang motor gang). Data analysis technique that used in this watchfulness uses data analysis model interactive mills and Huber man, by using data validity audit technic that is extension and triangulating.From watchfulness result demoes that communication strategy that done Policeman Resort city Pekanbaru in overcome motor gang, among others pass to approach persuasive and educative, do agreement, routine raid with does special. As to factors that causes the slow policeman resort city Pekanbaru in overcome motor gang that is caused by mobile character under communication from society in supports program and activity Polresta Pekanbaru in overcome motor gang, besides found between staff that go down leisure with area quantity that must be pacified from motor gang. while follow society that cause the slow Polresta Pekanbaru in overcome this motor gang caused by socialization under communication hits motor gang eradication by police apparatus to also to society.Keyword : Communication, communication strategy, causes, motor gang